The Lonely Hearts Hotel [large type] - O'Neill, Heather (Thorndike Press, a part of Gale, Cengage Learning, 2017)
With echoes of The Night Circus, this is a spellbinding story about two gifted orphans -- in love with each other since they can remember -- whose childhood talents allow them to rewrite their future. With her musical language and extravagantly realized world, Heather O'Neill enchants us with a novel so magical there is no escaping its spell.